The effect of lumbar multifidus cross-sectional areas on transforaminal epidural steroid injection: An observational clinical study - SAÇAKLIDIR, REKİB; SOYDEMİR, EFE; ŞENCAN, SAVAŞ; GÜNDÜZ, OSMAN HAKAN (My University, 2023)
OBJECTIVES: Multifidus has an important role in spinal stability, and multifidus degeneration causes long-term disability and low back pain. This study aimed to investigate the effect of multifidus cross-sectional area on transforaminal epidural steroid injections (TFESI). METHODS: Patients with single-level disc herniation were included in the study. Total multifidus cross-sectional area (TM-CSA) and functional cross-sectional area (FM-CSA) were measured from axial T2 MRI of the patients, and FM-CSA/TM-CSA ratio was calculated for determination of muscle degeneration or fat infiltration. Numerical Rating Scale (NRS) scores at the pre-injection, 3rd week, and 3rd month visits were recorded. A decrease of 50% or more in the NRS score in the 3rd month was accepted as a treatment success (TS), and patients were divided into TS and treatment failure groups. RESULTS: A total of 120 patients were included in the study; 57 of the patients were female, and 63 of them were male. Of the patients included in the study, 68 had herniation at the L5-S1 disc level and 52 had herniation at the L4-L5 disc level. FM-CSA and FM-CSA/TM-CSA ratio were found to be significantly lower below the disc herniation level on the affected side (p<0.05). The affected side TM-CSA and FM-CSA were higher in the TS group and TM-CSA/FM-CSA ratios were equal in both groups. CONCLUSION: Multifidus CSA was found to be lower on the affected side. However, the effect of multifidus CSA on the success of TFESI has not been determined.

Amaç: Multifidus spinal stabilitede önemli bir role sahip olup multifidus dejenerasyonu uzun dönemde bel ağrısı ve engelliliğe neden olmaktadır. Bu çalışmada, multifidus kesit alanının transforaminal epidural steroid enjeksiyonu tedavisi üzerine olan etkisinin araştırılması amaçlandı. Gereç ve Yöntem: Tek seviye disk hernisi olan hastalar çalışmaya dahil edildi. Hastaların aksiyel T2 manyetik rezonans görüntülerinden total multifidus kesit alanı ve fonksiyonel kesit alanı ölçüldü ve kas dejenerasyonu veya yağ dokusunun tespiti için fonksiyonel kesit alanı/total multifidus kesit alanı oranı hesaplandı. Enjeksiyon öncesi, üçüncü hafta ve üçüncü ay takiplerinde sayısal ağrı derecelendirme ölçeği skorları kaydedildi. Tedavi başarısı olarak üçüncü ayda sayısal ağrı derecelendirme ölçeği skorlarında %50 ve üzeri azalma kabul edildi ve hastalar tedavi başarısına ulaşanlar ve ulaşamayanlar olarak iki gruba ayrıldı. Bulgular: Toplam 120 hasta çalışmaya dahil edildi; hastaların 57’si kadın, 63’ü erkekti. Çalışmaya dahil edilen hastaların 68’inde L5-S1 disk seviyesinde herniasyon, 52’sinde L4-L5 disk seviyesinde herniasyon mevcuttu. Fonksiyonel kesit alanı ve fonksiyonel kesit alanı/total multifidus kesit alanı oranı etkilenen tarafta disk hernisi seviyesinin altında anlamlı derecede düşük saptandı (p<0,05). Etkilenen tarafta total multifidus kesit alanı ve fonksiyonel kesit alanı tedavi başarısına ulaşan grupta daha yüksekti ve total multifidus kesit alanı/fonksiyonel kesit alanı oranlarında iki grup arasında fark saptanmadı. Sonuç: Etkilenen tarafta multifidus kesit alanı daha düşük bulunmasına rağmen multifidus kesit alanının transforaminal epidural steroid enjeksiyonu tedavi başarısı üzerine etkisi saptanmamıştır
Lomber multifidus kesit alanının transforaminal epidural steroid enjeksiyonu üzerine etkisi: Gözlemsel klinik çalışma
Keywords: Tıp; Cerrahi Tıp Bilimleri; Anesteziyoloji; Sağlık Bilimleri; Medicine; Surgery Medicine Sciences; Anesthesiology; Health Sciences; Klinik Tıp (MED); Klinik Tıp; ANESTEZİYOLOJİ; Clinical Medicine (MED); CLINICAL MEDICINE; ANESTHESIOLOGY; Anesteziyoloji ve Ağrı Tıbbı; Anesthesiology and Pain Medicine; Lomber disk hernisi; epidural enjeksiyonlar; paraspinal kaslar; multifidus